Respostas
respondido por:
7
Temos a expressão:
(- 5).(- 1,8) - (+7).(+1,2)
=> Em 1º lugar ....multiplicações e divisões:
(9) - (8,4)
=> Em 2º lugar ...somas e subtrações
(9) - (8,4) donde resulta ...0,6
(- 5).(- 1,8) - (+7).(+1,2) ---> 0,6
Espero ter ajudado
(- 5).(- 1,8) - (+7).(+1,2)
=> Em 1º lugar ....multiplicações e divisões:
(9) - (8,4)
=> Em 2º lugar ...somas e subtrações
(9) - (8,4) donde resulta ...0,6
(- 5).(- 1,8) - (+7).(+1,2) ---> 0,6
Espero ter ajudado
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás